Chlamydia pneumoniae and asthma. Issue 4 (1st April 1998) - Cook, P J; Davies, P; Tunnicliffe, W; Ayres, J G; Honeybourne, D; Wise, R
Abstract : BACKGROUND: This study was designed to test the association of Chlamydia pneumoniae infection with asthma in a multiracial population, after adjustments for several potential confounding variables. METHODS: Antibodies to C pneumoniae were measured by microimmunofluorescence in 123 patients with acute asthma, 1518 control subjects admitted to the same hospital with various non-cardiovascular, non-pulmonary disorders, and 46 patients with severe chronic asthma, including some with "brittle" asthma. Acute infection or reinfection was defined by titres of IgG of ⩾512 or IgM ⩾8 or a fourfold rise in IgG, and previous infection by IgG 64–256 or IgA ⩾8. Logistic regression was used to control for likely confounders, including ethnic origin, age, sex, smoking habit, steroid medication, diabetes mellitus and social deprivation, on antibody levels. RESULTS: Antibody titres consistent with acute C pneumoniae infection were found in 5.7% of patients with acute asthma and 5.7% of control patients, while 14.6% of patients with acute asthma and 12.7% of control patients had titres suggesting previous infection. These two groups did not differ significantly. However, titres suggesting previous infection were found in 34.8% of patients with severe chronic asthma: the difference between this group and the control group was statistically significant with an adjusted odds ratio of 3.99 (95% confidence interval 1.60 to 9.97). CONCLUSIONS: These data raise important questions about the previously demonstrated association of C pneumoniae infection with asthma, and suggest that future studies of this association should give particular attention to the presence or absence of a history of severe chronic asthma.